Epidemiology, Trends, Risk Factors and Clinical Outcomes of Dengue Fever among Adolescents and Young Adults in Dhaka City of Bangladesh (Bangladesh Journal of Infectious Diseases, 2025)
Background: Dengue fever is an escalating public health concern in Bangladesh, with Dhaka City experiencing recurrent epidemics that disproportionately affect adolescents and young adults.Objective: This study was aimed to analyse fourteen years of surveillance data to characterize demographic, socioeconomic, and seasonal determinants of dengue morbidity and mortality in this vulnerable population.Methodology: A retrospective, record-based design was applied using hospital surveillance data and Directorate General of Health Services (DGHS) databases from January 2010 to November 2023. All laboratory-confirmed cases were included based on national diagnostic criteria (NS1 antigen, IgM, or RT-PCR). Data were compiled, cleaned, and analyzed using descriptive statistics to summarize demographic patterns, while chi-square tests and logistic regression examined associations between age, sex, socioeconomic status, residential setting, and severity. Correlation analysis assessed seasonal effects of rainfall.Results: Approximately 117,000 confirmed cases were identified. The mean age was 18.7 years (SD ± 2.1); late adolescents (18 to 20 years) comprised 46.0% of cases, with males accounting for 55.0%, though females showed 15.0% higher hospitalization and complication rates (p < 0.05). Low-income youth experienced 30% higher prevalence, while those in informal settlements had 1.4-fold greater odds of infection (95% CI: 1.2–1.7). First-time infections accounted for 84.0% of cases, while recurrent infections nearly doubled the odds of severe dengue (OR 1.92; 95% CI: 1.55–2.38). Annual epidemics peaked in 2019 (101,354 cases, 179 deaths), 2022 (62,382 cases, 281 deaths), and 2023 (69,483 cases, 327 deaths), with CFR rising to 0.47%. Monsoon months showed a 50.0% to 60.0% increase in cases, strongly correlated with rainfall (r = 0.71, p < 0.001).Conclusion: Adolescents in Dhaka city face disproportionate dengue risks shaped by social inequities, recurrent infection, and seasonal climate variation. Future studies should evaluate behavioral, nutritional, and immunological determinants in greater depth, while public health efforts prioritize youth-focused education, strengthened healthcare capacity, and climate-sensitive surveillance to mitigate rising severity.Bangladesh Journal of Infectious Diseases, June 2025;12(1):3-17